Dynamism of Waqf of Unit Trusts from Shariah Perspective - Sulaiman, Syahnaz; Hasan, Aznan (Academy of Islamic Studies, University of Malaya, 2017)
The majority of waqf assets available across the Muslim world today consist of immovable property such as land and buildings; all of which conform to Shariah principles. In line with the global changes and current needs, dedicated assets for the purpose of waqf have evolved from movable to immovable assets to include cash, stocks and bonds. However, the discussion pertaining to Shariah ruling and the procedures of managing this category of waqf assets is still limited. The concept of waqf of unit trusts is still new and more research needs to be carried out for better comprehension and implementation. The question arises with regards to the position of unit trust as the subject of waqf given that it has no distinct and permanent features which allow for it to be transferable from one hand to another. Accordingly, this study will discuss the Islamic legal ruling and the procedures of managing waqf of unit trusts within the framework of Islamic law. This study is qualitative in nature, involving document analyses of journal articles, books and policy documents as well as in-depth interviews with experts. The findings conclude that unit trusts have been regarded as a permissible waqf object. This study also outlines the procedure for a prudent management of waqf of unit trusts to ensure the application is consistent with the principles of Shariah.